Changes in Characteristics and Outcomes of Newly Initiated Physician-Led Home Visit Care Before and During the Coronavirus Disease 2019 Pandemic: A Multicenter Retrospective Study in Japan - Yu Sun; Ryohei Goto; Jun Hamano; Sayaka Nin; Shoichi Masumoto; Natsuki Kajikawa; Takashi Inaba; Shuhei Hamada; Noriyuki Kimura; Saki Fukai; Mitsuaki Ishii; Takeya Kawasaki; et al. (Journal of Primary Care & Community Health)
Introduction: The coronavirus disease 2019 (COVID-19) pandemic disrupted healthcare systems and increased the need for home healthcare. This study examined how the pandemic influenced the characteristics and outcomes of newly initiated physician-led home visit care in Japan, particularly focusing on patients with cancer. Methods: We conducted a multicenter retrospective study using medical records from 6 home care clinics and hospitals in Ibaraki Prefecture, Japan. Patients who began physician-led home visit care between April 2019 and March 2023 were included. We compared patient characteristics, care duration, and outcomes between the pre-pandemic (April 2019 to March 2020) and pandemic (April 2020 to March 2023) periods. To examine changes before and during the pandemic, we conducted logistic regression analysis using the pandemic indicator as the exposure and home death within 1, 3, and 6 months as the outcome, adjusting for patient factors. We also examined the interaction between cancer status and the pandemic period. Results: A total of 1922 patients were included. The number of patients initiating home visit care slightly increased after the onset of the COVID-19 pandemic. The proportion of patients with cancer significantly increased during the pandemic (pre-pandemic: 37.5% vs. during-pandemic: 43.0%, P  = .046). Home deaths within 1 month significantly increased during the pandemic compared to the pre-pandemic period (odds ratio (OR) [95% confidence interval (CI)]: 1.87 [1.33-2.63]). However, in the model including the interaction term, the main effect of the pandemic indicator alone disappeared, while the interaction between cancer and the pandemic showed a strong association with home death (OR [95% CI]: 9.33 [5.29-16.47]). Similar results were observed for home deaths within 3 and 6 months. Conclusions: Our findings suggest that home visit clinics adapted to the increased demands for home-based end-of-life care, particularly for patients with cancer during the pandemic. These findings highlight the need for strategic support and resource planning to manage surges in home-based care during health crisis.